1988
DOI: 10.1007/bf00052703
|View full text |Cite
|
Sign up to set email alerts
|

When is a science analogy like a social studies analogy? A comparison of text analogies across two disciplines

Abstract: This textbook survey analyzes the construction and use of analogies in social science texts and compares the results to an earlier analysis of physical science texts. Although the results indicate that the categories in the Curtis and Reigeluth classification system for analogy construction were consistent across disciplines, several differences were revealed related to how and when the analogy is used as an instructional design strategy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0
4

Year Published

1994
1994
2015
2015

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(16 citation statements)
references
References 5 publications
0
12
0
4
Order By: Relevance
“…Mastering these paradigms means the ability to apply them to a broad variety of tasks. In the context of education, Curtis (1988) showed that the acquisition of inductive reasoning is applicable even in classroom instruction.…”
Section: Theory and Programmementioning
confidence: 99%
“…Mastering these paradigms means the ability to apply them to a broad variety of tasks. In the context of education, Curtis (1988) showed that the acquisition of inductive reasoning is applicable even in classroom instruction.…”
Section: Theory and Programmementioning
confidence: 99%
“…Cf. Curtis (1988) and Iding (1997). Is the previous point connected with the nature of the academic disciplines and corresponding opinions on, and the content of, school subjects?…”
Section: Discussionmentioning
confidence: 99%
“…Curtis ve Reigeluth (1984), yapmış oldukları araştırmada inceledikleri kitaplardaki analojilerin büyük bir bölümünün zenginleştirilmiş analoji türünde olduğu sonucuna ulaşmışlardır. Benzer şekilde, Curtis (1988)'in yapmış olduğu araştırmada 26 sosyal bilgiler kitabının incelenmesi neticesinde tespit edilen 64 analojinin yaklaşık %50'sinin zenginleştirilmiş türde olduğu sonucuna ulaşılmıştır. Kaya (2010)' nın çalışmasında ise genişletilmiş analojilerin ağırlıklı olduğu göze çarpmaktadır.…”
Section: Tartışma Sonuç Ve öNerilerunclassified
“…12. sınıf ders kitabında sadece sözel türde analoji tespit edilmesi, sınıf seviyesiyle orantılı olarak öğrencilerin somutlaştırma kabiliyetlerinin artmasıyla açıklanabilir ancak yine de analojilerin resimlerle desteklenmesi bu tekniğin etkililiği açısından önem taşımaktadır. Curtis (1988)'in çalışmasında sosyal bilimlerde sözel resimsel analojilerin sıklıkla kullanıldığına dair bulgular, önceki açıklamaları destekler niteliktedir.…”
Section: Tartışma Sonuç Ve öNerilerunclassified
See 1 more Smart Citation